Atomic Structure and Its Connection to The Quranic Verses' Context - Abdul Mujala; Muhammad Reza; Kana Puspita (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2023)
Abstract: The growth of science in the twenty-first century, particularly in chemistry, is critically dependent on the integration of science and the Qur'an. Since numerous verses in the Qur'an disclose the fundamental principles of chemistry, such as the size of an atom, the integration of science and the Qur'an is nothing new in modern science, especially chemistry. As a result, this article will go into further detail regarding the atomic structure's physical setting and how it relates to Qur'anic verses. Writing this paper involved conducting literature searches on both contemporary science and Qur'anic interpretations of atomic structure. The word